2018
DOI: 10.5964/jnc.v3i3.113
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of basic cognitive skills on the relation between math performance and math anxiety

Abstract: What causes math anxiety? According to a cognitive deficits view, early weaknesses in basic number and spatial skills lead to poor performance and hence negative affect. A strong version of this view suggests that the relation between math anxiety and math performance among adults will be explained by deficits in spatial and basic number skills. In the present research, we tested a model to account for the relations among math anxiety, math performance, and cognitive skills (i.e., working memory, basic number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
3
23
4
Order By: Relevance
“…Supporting the argument that math anxiety is activated specifically during involvement with learnt numerical information, math-anxious individuals were found to exhibit a deficit in the counting (an exact symbolic linguistic skill strongly associated with formal schooling; Gallistel and Gelman, 1992; Cordes et al, 2001) but not in the subitizing range (an exact symbolic linguistic skill that usually develops in the preschool years), with working memory as a mediator of this effect (Maloney et al, 2010). Moreover, math-anxious individuals showed reduced accuracy in mental representations of learnt symbolic but not innate non-symbolic numerical magnitudes or innate spatial abilities (Maloney et al, 2011; Dietrich et al, 2015; Douglas and LeFevre, 2018).…”
Section: Environmental Factors: Mediating and Moderating Processesmentioning
confidence: 99%
“…Supporting the argument that math anxiety is activated specifically during involvement with learnt numerical information, math-anxious individuals were found to exhibit a deficit in the counting (an exact symbolic linguistic skill strongly associated with formal schooling; Gallistel and Gelman, 1992; Cordes et al, 2001) but not in the subitizing range (an exact symbolic linguistic skill that usually develops in the preschool years), with working memory as a mediator of this effect (Maloney et al, 2010). Moreover, math-anxious individuals showed reduced accuracy in mental representations of learnt symbolic but not innate non-symbolic numerical magnitudes or innate spatial abilities (Maloney et al, 2011; Dietrich et al, 2015; Douglas and LeFevre, 2018).…”
Section: Environmental Factors: Mediating and Moderating Processesmentioning
confidence: 99%
“…Studies investigating the link between MA and math ability using a comprehensive test battery of both basic number processing and general cognitive abilities are scarce. A very recent contribution comes from Douglas and Lefevre [52] who investigated the influence of cognitive abilities and basic number skills on MA using SEM. They found that there was no direct link between neither cognitive abilities nor basic number skills to MA.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the authors found that complex math performance fully mediated the relations between basic cognitive skills and MA. In addition, there was no direct link between basic number processing and MA [52]. The link between MA and math abilities is likely complex and, as Douglas and Lefevre [52] noted, there are likely several factors that may be at play.…”
Section: Introductionmentioning
confidence: 99%
“…The Calculation Fluency Test (CFT) was used to index the participants' arithmetic ability (Douglas & LeFevre, ). The CFT consists of three subtests involving two‐term arithmetic problems on three separate A4 pages, and each subtest contains 60 problems.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, Cronbach's α s for the addition, subtraction, and multiplication subtests were .95, .97, and .97, respectively. To simplify the subsequent analyses, the sum of the three subtests was used as a measure of arithmetic calculation ability (e.g., Douglas & LeFevre, ).…”
Section: Methodsmentioning
confidence: 99%